Comparison of the Response to Pulpal Sensibility Tests in Well-Controlled and Uncontrolled Type II Diabetes Mellitus Patients: A Cross-Sectional Study - Fatemeh Owlia; Faezeh Zarezadeh; Sara Jambarsang; Maryam Kazemipoor (International Journal of Dentistry)
Introduction. Diabetes mellitus is a metabolic disorder in which impairment of sensory fibers would be anticipated. The present study would assess the dental pulp response to cold and EPT sensibility tests in patients with type 2 diabetes, both well-controlled and uncontrolled. Materials and Methods. One hundred two maxillary central incisors, belonging to participants aged 35–67 years, were included in this survey. At last, 51 diabetic patients were allocated to each group of well-controlled (HbA1C < 7) and uncontrolled (HbA1C ≥ 7). Electric and cold pulpal vitality tests were conducted for all teeth. Statistical analysis was performed with Student’s t-test, the chi-square test, and the multiple linear regression model. A P value less than 0.05 was considered significant. Results. Based on the results of this study, the mean value of response to EPT was 4.51 ± 2.06 and 4.41 ± 1.85 in well-controlled and uncontrolled diabetic patients, respectively. Also, the pulpal responses to cold and EPT tests had no significant differences between the two groups (P>0.05). Conclusion. Tooth responses to the cold and EPT sensibility tests were not different in well-controlled and uncontrolled diabetic patients. Despite no statistically significant correlation, male diabetic patients in the uncontrolled group showed a lower sensory response threshold to EPT compared to a well-controlled group.